The Concept of Faith in Ibn Taimiyah's Perspective Between Belief, Verbal and Action - Assyifa Dalillah; Ela Fadhalah; Ekawati Ekawati (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
The concept of faith in Islam has been a classic debate among Islamic scholars. Ibn Taymiyyah, a key figure in Islamic thought, provided a comprehensive definition of faith, encompassing conviction in the heart, verbal affirmation, and bodily actions. He argued that faith can increase and decrease according to one's deeds. This view rejects the understanding of faith as merely a belief in the heart or merely verbal, as some groups believe. This article aims to examine in depth Ibn Taymiyyah's thoughts on the nature of faith, as well as the rational and intellectual foundations used in his arguments. Using a descriptive qualitative method with a literature review approach, this paper reveals that Ibn Taymiyyah emphasized the importance of balancing the theoretical and practical aspects of faith. The implication is that faith is not merely internally acknowledged but must be demonstrated through concrete righteous deeds. This concept is relevant in the contemporary context as an effort to shape a complete Muslim personality in both belief and action.